Seroprevalence of Foot and Mouth Disease Virus (FMDV) and associated risk factors in unvaccinated sheep and goats in Pyawbwe and Meikhtila townships of Myanmar (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: In this study, a serological survey was conducted in unvaccinated sheep and goat populations at Pyawbwe and Meikhtila townships of Mandalay region in Myanmar to determine the seroprevalence and associated risk factors of foot and mouth disease (FMD).Materials and methods: A total of 110 sheep and 107 goat sera samples were randomly collected from Pyawbwe. Similarly, 108 sheep and 109 goat sera were collected from Meikhtila. All samples were tested for the presence of non-structural protein (NSP) specific antibodies to FMD virus (FMDV) by Ceditest FMDV-NSP Enzyme-lined Immunosorbent Assay (ELISA), and were confirmed by Liquid Phase Blocking ELISA (LPB ELISA) .Results: Overall seroprevalence was 42.4%(n=184/434) by Ceditest-NSP ELISA, and 46.8%(n=203/434) by LPB ELISA against FMDV serotype O. The presence of antibodies against FMDV serotype O was higher (P